Camping out in California. - Rideout, J. B., Mrs. (San Francisco, R.R. Patterson, 1889)
Mrs. Jacob Rideout of California was a member of an 1888 camping party in northern California. Camping out in California (1889) describes their adventures at the redwood forests, the coast near Mendocino, Sonoma, the Santa Clara Valley, a G.A.R. conclave in Santa Cruz, Mount St. Helena, and a side trip to San Francisco.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; Camping; Women -- California